Uji Efektivitas Ekstrak Etanol Daun Bugenvil (Bougenvillea Spectabilis) terhadap Penurunan Kadar Kolestrol Total Mencit Yang di Induksi Pakan Tinggi Lemak - Rifda Naufa Lina; Sofiyatul Nurul Jannah (Biomedika, 2019)
Cholesterol is a natural substance with fat-like physical properties that has a steroid group. The increase in cholesterol causes deposition in the walls of blood vessels which can cause narrowing and hardening of the arteries or atherosclerosis which can increase the risk of coronary heart disease (CHD). Flavonoids, alkaloids, steroids, and tannins in bougainvillea leaves are thought to reduce total cholesterol levels. This study aims to determine the effectiveness of bougainvillea leaf ethanol extract (Bougainvillea spectabilis) to decrease the total cholesterol level of mice (Mus musculus) induced by high-fat diet for 21 days. This study true experimental using 25 male mice (Mus musculus) divided into 5 groups.. In the dose I, II, III treatment group were given bougainvillea leaf ethanol extract with doses of 40 mg/kgBW, 80 mg/kgBB and 160 mg/kgBB, negative controls were given CMC-Na and positive controls were given simvastatin. Giving is done orally for 14 days. The results of the study were analyzed using One-Way ANOVA analysis test and the results obtained p=0,000. Furthermore, the Post Hoc Tukey test was carried out, the results of which were not significantly different between positive controls and dose III. So, the effective dose of ethanol extract of bougenvillea leaves in decreasing total cholesterol levels in mice is dosis III (160 mg/kgBB).